Underground carbon sequestration as a component of decarbonization in anthropogenic activity - Goldobin, D.S.; Baryakh, A.A. (Perm Federal Research Centre Journal, 2024)
The article discusses why it is appropriate to talk about carbon utilization even in cases where the goal is to reduce carbon dioxide emissions into the environment. An explanation is given as to why underground carbon dioxide burial (geosequestration) is the main feasible solution for the decarbonization of anthropogenic activity at the planetary scale. A brief review of existing or promising practices of carbon dioxide geosequestration is provided. The economic and technological aspects of the implementation of geosequestration projects, affecting their feasibility, are viewed, as well as the relevant statistics of such projects over the first two decades of the XXI century. In particular, the extremely low percentage of implementation of planned projects is noted in the majority of industrial sectors consuming fossil hydrocarbon fuels. The regional aspect of the problem is considered in relation to the work of industrial companies of the Perm Region and their foreign economic activity under the conditions of the enacted and planned legislation. The available potential of the regions’s subsoil for geosequestration of carbon dioxide is stated - oil collectors, coal seams of the sealed mines of the Kizelovsky basin, salt deposits of the Verkhnekamsky deposit.